Mild covalent functionalization of single-walled carbon nanotubes highlighted by spectroscopic ellipsometry. (January 2016) - Battie, Yann; Dossot, Manuel; Allali, Naoual; Mamane, Victor; Naciri, Aotmane En; Broch, Laurent; Soldatov, Alexander V.
Abstract: Single-walled carbon nanotubes (SWCNT) synthesized using the HiPco ® process and purified thereafter were submitted to two covalent functionalization processes: i) a mild oxidation in a concentrated HNO3 solution using microwave irradiation and ii) a radical functionalization to graft methoxyphenyl groups. The samples were analyzed by Raman spectroscopy and spectroscopic ellipsometry in the energy window 0.07–4.96 eV. The complex dielectric function was analytically calculated in order to extract the real (εr ) and imaginary (εi ) parts of this function vs. the incident energy of the light. The ellipsometric data in the infrared part of the spectrum revealed that process i) mainly affected the amorphous carbon deposited on the surface of SWCNTs while process ii) strongly changed the electronic nature of the film due to a charge transfer between methoxyphenyl groups and SWCNTs. These results demonstrate the richness of information that spectroscopic ellipsometry is able to bring about on an entire carbon nanotube ensemble compared to Raman spectroscopy, while not suffering from limitation on their electronic structure and/or aggregate state/presence of surfactants.